Mapping the dynamics of brain perfusion using functional ultrasound in a rat model of transient middle cerebral artery occlusion. Issue 1 (January 2017) - Brunner, Clément; Isabel, Clothilde; Martin, Abraham; Dussaux, Clara; Savoye, Anne; Emmrich, Julius; Montaldo, Gabriel; Mas, Jean-Louis; Baron, Jean-Claude; Urban, Alan
Following middle cerebral artery occlusion, tissue outcome ranges from normal to infarcted depending on depth and duration of hypoperfusion as well as occurrence and efficiency of reperfusion. However, the precise time course of these changes in relation to tissue and behavioral outcome remains unsettled. To address these issues, a three-dimensional wide field-of-view and real-time quantitative functional imaging technique able to map perfusion in the rodent brain would be desirable. Here, we applied functional ultrasound imaging, a novel approach to map relative cerebral blood volume without contrast agent, in a rat model of brief proximal transient middle cerebral artery occlusion to assess perfusion in penetrating arterioles and venules acutely and over six days thanks to a thinned-skull preparation. Functional ultrasound imaging efficiently mapped the acute changes in relative cerebral blood volume during occlusion and following reperfusion with high spatial resolution (100 µm), notably documenting marked focal decreases during occlusion, and was able to chart the fine dynamics of tissue reperfusion (rate: one frame/5 s) in the individual rat. No behavioral and only mild post-mortem immunofluorescence changes were observed. Our study suggests functional ultrasound is a particularly well-adapted imaging technique to study cerebral perfusion in acute experimental stroke longitudinally from the hyper-acute up to the chronic stage in the same subject.